RNA Interference: A Novel Source of Resistance to Combat Plant Parasitic Nematodes - Banerjee, Sagar; Banerjee, Anamika; Gill, Sarvajeet S.; Gupta, Om P.; Dahuja, Anil; Jain, Pradeep K.; Sirohi, Anil (Frontiers in Plant Science, 2017)
Plant parasitic nematodes cause severe damage and yield loss in major crops all over the world. Available control strategies include use of insecticides/nematicides but these have proved detrimental to the environment, while other strategies like crop rotation and resistant cultivars have serious limitations. This scenario provides an opportunity for the utilization of technological advances like RNA interference (RNAi) to engineer resistance against these devastating parasites. First demonstrated in the model free living nematode, Caenorhabtidis elegans; the phenomenon of RNAi has been successfully used to suppress essential genes of plant parasitic nematodes involved in parasitism, nematode development and mRNA metabolism. Synthetic neurotransmitants mixed with dsRNA solutions are used for in vitro RNAi in plant parasitic nematodes with significant success. However, host delivered in planta RNAi has proved to be a pioneering phenomenon to deliver dsRNAs to feeding nematodes and silence the target genes to achieve resistance. Highly enriched genomic databases are exploited to limit off target effects and ensure sequence specific silencing. Technological advances like gene stacking and use of nematode inducible and tissue specific promoters can further enhance the utility of RNAi based transgenics in plant parasitic nematodes.